Design, Construction, and Control Tracking of Solar Thermal Concentrator by Using PLC in Erbil (Journal of Engineering, 2023)
This paper demonstrates the construction designing analysis and control strategies for fully tracking concentrated solar thermal by using programmable logic control in the city of Erbil-Iraq. This work used the parabolic dish as a concentrated solar thermal. At the focal point, the collected form of energy is used for heating a (water) in the receiver, analyzing this prototype in real-time with two different shapes of the receiver and comparing the results. For tracking the parabolic dish, four light-dependent resistors are used to detect the sun's position in the sky so that the tracking system follows it to make the beam radiation perpendicular to the collector surface all of the time during the day for maximum solar power energy. This work discusses the essential stages of a two-axis prototype; implementation, solar-location strategy, the analysis in terms of theory, structural design, and material. For two-axis-prototype is implemented with the help of programmable logic control -Siemens (S7-1200) as a control unit. This study results show that a parabolic dish tracker with a cylindrical conical receiver obtains 15.25% Improved efficiency in comparison to the cylindrical receiver. According to the testing results of the prototype design, both shapes of the receiver are convenient for steam production.